Respon Varietas Unggul Kacang Tanah terhadap Cekaman Salinitas Responses of Groundnut Varieties to Salinity Stress - Taufiq, Abdullah; Kristiono, Afandi; Harnowo, Didik (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2015)
Soil salinity has negative effect on crop growth and crop productivity. Information on the response of groundnut varieties to salinity is required for varietal selection adaptable to saline soil condition. The research was conducted at the greenhouse of Indonesian Legume and Tuber Crops Research Institute (Iletri), Malang, East Java from July to September 2013. The objective of the research was to study the effect of salinity on groundnut growth.Ten groundnut varieties, consisted of seven varieties of Spanish type and three varieties of Valencia type, were tested on six levels of soil salinity. The treatment combinations were arranged in randomized complete block design, replicated four times. The soil salinity level was obtained by treating soil media using sea water dilution. Observations were made on electrical conductivity (EC) of the soil, plant height, leaf chlorophyll content index, shootand root dry weight, number and dry weight of pods, and number and dry weight of normal seeds. Results showed that increasing the salinity level inhibited both vegetative and generative growth and the critical age to the plants affected by salinity was 45-65days after sowing. All variables of plant growth and yield components decreased with the increase of salinity level. The highest EC value of the soil for groundnut planting to produce pods and seeds was 1.60-1.84 dS/m. Based on the growth variables, varieties of Valencia-type semed to be more tolerant to salinity than did Spanish-type, but there was no tolerance difference based on crop yield and yield components between the two groundnut groups. Higher tolerance of Valencia type was probably due to its ability to absorb and translocate more K in saline conditions. Among the Valencia type varieties tested, Domba variety indicated the most tolerance.